PERENCANAAN BENDUNGAN TUGU KABUPATEN TRENGGALEK - Tedy Wibowo; Rizki Dwi Putro; Sri Sangkawati; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Tugu Dam is a dam that was built to needs of irrigation water and raw water needs necessary. It had built on the Keser River with catchmen area of river is 43,06 km2, with a length of river is 9,295 km. Administratively located in the Nglinggis Village, Tugu Subdistrict, Trenggalek Regency, East Java Province and is geographically located at position 8˚1 '- 8˚3' south latitude and 111˚34 '- 111˚37' east longitude. Before the Tugu Dam was built, water irrigation fulfillment necessary done by taking water from the Keser River, but water irrigation requirement not maximum because the water taking from the Keser River done with pump system. Tugu Dam is expected to fulfill the irrigation water of Tugu irrigationwith a total area of 1.106 hectare, and fulfill of the raw water in Nglinggis, Pucang Anak, Dermosari, Winong and Tegaren Village of Tugu District on Trenggalek Regency with a projected total populations in 2042 is 19.589 inhabitants. Before planning a dam, the initial step is the hydrological analysis with the result that be discovered gauge the dependable discharge, needs water discharge and flood discharge. In the Tugu Dam planning dependable discharge used is the discharge with probability 80%. Water needs value to fulfill the irrigation water requirement is 0,81 liters/sec/hectare or water needs discharge for water irrigation is 0,90 m3/sec and water needs discharge for raw water is 0,03 m3/sec. Flood discharge using HSS Gama I method for return period of 1000 years of 667,70 m3/sec is used as the basic for search flood analysis (flood routing)by means of the spillway to obtain the dimensions of the main dam and the spillway. Tugu Dam planned using the rock fill dam material with watertight clay core with a slope of 1 : 2,25 in the upstream and 1 : 2,00 in the downstream. Elevated of dam is 69,00 m, the wide of the peak is 12,00 m, wide of the base dam is 301,00 m and full length of the dam is 309,26 m with a 30-year design lifetime of the dam and reservoir volume of 6.12 million m3. Spillway design with specific such as OGEE peak wide of 10,00 m, USBR type II for stilling basin with pool dimensions of 10x55 m and 553,00 m long tunnel deterrent with a diameter of 3,00 m with a number of 2 pieces. Tugu Dam planned at a cost of +495,50 billions rupiahs, and planned implementation time +560 working days.